Collaboration between specialties for respiratory allergies in the International Classification of Diseases (ICD)-11. Issue 1 (December 2017) - Tanno, Luciana; Calderon, Moises; Linzer, Jeffrey; Chalmers, Robert; Demoly, Pascal
Abstract Background The International Classification of Diseases (ICD) has been grouping the allergic and hypersensitivity disorders involving the respiratory tract under topographic distribution, regardless of the underlying mechanisms, triggers or concepts currently in use for allergic and hypersensitivity conditions. In order to strengthen awareness and deliberate the creation of the new "Allergic or hypersensitivity disorders involving the respiratory tract" section of the ICD-11, we here propose make the building process public. Methods The new frame has been constructed to cover the gaps previously identified and was based on consensus academic reports and ICD-11 principles. Constant and bilateral discussion was kept with relevant groups representing specialties and resulted in proposals submission into the ICD-11 online platform. Results The "Allergic or hypersensitivity disorders involving the respiratory tract" section covers 64 entities distributed across five main categories. All the 79 proposals submitted resulted from an intensive collaboration of the Allergy working group, relevant Expert working groups and the WHO ICD governance. Conclusion The establishment of the ICD-11 "Allergic or hypersensitivity disorders involving the respiratory tract" section will allow the dissemination of the updated concepts to be used in clinical practice by many different specialties and health professionals.